A Multi-institutional Case Series With Review of Point-of-Care Ultrasound to Diagnose Malrotation and Midgut Volvulus in the Pediatric Emergency Department. Issue 6 (June 2019) - Garcia, Angélica Marie; Asad, Imran; Tessaro, Mark O.; Sivitz, Adam; Osborn, Katharine; Shaahinfar, Ashkon; Leung, Stephanie K.; Rowe, Erin; Riera, Antonio
Abstract : Abstract: Point-of-care ultrasound can be used to screen for malrotation with and without volvulus in the newborn with bilious vomiting, as well as children with unexplained intermittent abdominal pain. We discuss cases where infants and children presenting to pediatric emergency departments with bilious vomiting and/or intermittent abdominal pain were initially screened for small bowel pathology with point-of-care ultrasound. Bedside findings suggestive of midgut volvulus were confirmed with radiology-performed ultrasound or upper gastrointestinal fluoroscopy. In all cases, operative findings were consistent with malrotation of the small bowel with or without evidence of midgut volvulus.